Work resources and well-being at work : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Auckland, New Zealand - Solomons, Kim (Massey University, 2011)
This study investigated the importance of occupational resources within the context of a sample group of Corrections Officers in New Zealand. It was hypothesised that resources including decision latitude, social support from colleagues and supervisors, and satisfaction with supervisors and job training, would make an impact on all stages of the Stress – Appraisal process, with the intention to illustrate that resources can have positive influences on a potentially demanding role. Relationships between resources and the variables of the Stress – Appraisal model were tested using regression analysis. Results revealed that overall resources made small but significant contributions to appraisal, well-being, stress and all three outcomes; job satisfaction, affective commitment and intentions to stay, but not to coping and affect. The only resource to make an impact on emotion-focused coping was decision latitude. Decision latitude, satisfaction with job training and supervisor support were the three resources most valued in this sample group of Corrections Officers. In terms of the Stress –Appraisal model, regression analysis also indicated that threat appraisal was important to emotion and support focused coping, while challenge appraisal and emotion focused coping explained significant variance to positive affect. Negative affect was only influenced by emotion-focused coping and well-being and stress was significantly influenced by affect. Given the partial support of the impact of resources and the Stress – Appraisal model, this study concludes that resources are indeed important and can make an impact on positive outcomes, however more research is required in this area to investigate other factors such as personal dispositions that may also add variance in the understanding of positive outcomes and the well-being process.
Keywords: Work resources; Wellbeing; Job satisfaction; Job stress; Industrial psychology; Work psychology; Prison wardens; Corrections officers; New Zealand